2024
DOI: 10.1021/acsnano.4c02652
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared-II Imaging Revealed Hypothermia Regulates Neuroinflammation Following Brain Injury by Increasing the Glymphatic Influx

Wenzhong Li,
Bin Sun,
Xiaoyu Zhang
et al.

Abstract: Advanced in vivo imaging techniques have facilitated the comprehensive visual exploration of animal biological processes, leading to groundbreaking discoveries such as the glymphatic system. However, current limitations of macroscopic imaging techniques impede the precise investigation of physiological parameters regulating this specialized lymphatic transport system. While NIR-II fluorescence imaging has demonstrated advantages in peripheral lymphatic imaging, there are few reports regarding its utilization i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…The development of fluorescent dyes targeting live cells has attracted extensive attention, such as membrane potentials and kinase activities. Recently, NIR fluorescent molecules have been widely used in antibacterial research, cancer therapy, and biological detection and imaging. NIR fluorescent molecules have enabled organelle-specific imaging and live imaging of cancer cells, zebrafish, and tumor-bearing mice. Researchers reported a water-soluble plasma membrane (PM)-specific probe for PM imaging with excellent PM specificity and ultrafast staining capability . Another study reported a NIR aggregation-induced emission dye (AIE) for myelin imaging from nerve to brain tissues .…”
mentioning
confidence: 99%
“…The development of fluorescent dyes targeting live cells has attracted extensive attention, such as membrane potentials and kinase activities. Recently, NIR fluorescent molecules have been widely used in antibacterial research, cancer therapy, and biological detection and imaging. NIR fluorescent molecules have enabled organelle-specific imaging and live imaging of cancer cells, zebrafish, and tumor-bearing mice. Researchers reported a water-soluble plasma membrane (PM)-specific probe for PM imaging with excellent PM specificity and ultrafast staining capability . Another study reported a NIR aggregation-induced emission dye (AIE) for myelin imaging from nerve to brain tissues .…”
mentioning
confidence: 99%